2009
DOI: 10.2337/dc09-0284
|View full text |Cite
|
Sign up to set email alerts
|

Insomnia With Objective Short Sleep Duration Is Associated With Type 2 Diabetes

Abstract: OBJECTIVEWe examined the joint effects of insomnia and objective short sleep duration, the combination of which is associated with higher morbidity, on diabetes risk.RESEARCH DESIGN AND METHODSA total of 1,741 men and women randomly selected from Central Pennsylvania were studied in the sleep laboratory. Insomnia was defined by a complaint of insomnia with duration of ≥1 year, whereas poor sleep was defined as a complaint of difficulty falling asleep, staying asleep, or early final awakening. Polysomnographic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

19
351
4
8

Year Published

2012
2012
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 472 publications
(382 citation statements)
references
References 26 publications
19
351
4
8
Order By: Relevance
“…However, the mean TST in the insomnia group was greater than 5h, and no sub-group analysis was performed to compare TST below and above 5h 26 . In fact, an objective sleep duration of less than 5 h is necessary to increase the risk of diabetes 8,27 . The severity of sleep disturbance is a key component in metabolic control, as only severe sleep apnea is clearly related to the risk of impaired glucose metabolism 28 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the mean TST in the insomnia group was greater than 5h, and no sub-group analysis was performed to compare TST below and above 5h 26 . In fact, an objective sleep duration of less than 5 h is necessary to increase the risk of diabetes 8,27 . The severity of sleep disturbance is a key component in metabolic control, as only severe sleep apnea is clearly related to the risk of impaired glucose metabolism 28 .…”
Section: Discussionmentioning
confidence: 99%
“…A cross-sectional analysis revealed that insomnia with objective short sleep duration is associated with an increased risk of diabetes 8 . Hypothalamic-pituitary-adrenal (HPA) axis activity plays a role in hypertension and diabetes development 9,10 .…”
mentioning
confidence: 99%
“…[5][6][7][8][9][10][11] A large population-based Norwegian study suggested that after adjusting for confounding factors, insomnia remained a significant risk factor for rheumatic diseases, including fibromyalgia (odds ratio [OR], 2.05; 95 % confidence interval [CI], 1.51-2.79) and rheumatoid arthritis (OR, 1.87; 95 % CI, 1.29-2.52). 8 However, there is no systemic longitudinal evidence linking chronic insomnia with autoimmune diseases (AID).…”
Section: Electronic Supplementary Materialsmentioning
confidence: 99%
“…This is consistent with findings from our longitudinal analysis that poor sleep quality significantly increased the risk of diabetes. The cross-sectional study by Vgontzas et al, 136 did not find individual associations between insomnia and diabetes, or sleep duration and diabetes, but after examining the joint effects of insomnia and sleep duration, they found that compared to normal sleeping subjects (sleep duration of >6 hours), those with insomnia and with short sleep duration (<5 hours) were at increased risk of diabetes. Our sleep quality variable was composed of items other than insomnia and although we did not stratify on number of hours of sleep, we found a significant relationship between poor sleep quality and diabetes after adjusting for confounders including sleep duration.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, sleep duration and sleep quality have often been analyzed separately in both longitudinal and cross-sectional studies, and only very few studies have incorporated aspects of both sleep duration and quality into their analyses 135,136 . Sleep duration is measured by the number of hours a person sleeps in a day, and does not take into account the nature of the sleep.…”
Section: Resultsmentioning
confidence: 99%